The First Application of a Gd3Al2Ga3O12:Ce Single-Crystal Scintillator to Neutron Radiography - Kazuhisa Isegawa (MDPI AG, 2021)
Neutron radiography is regarded as complementary to X-ray radiography in terms of transmittance through materials, but its spatial resolution is still insufficient. In order to achieve higher resolution in neutron imaging, several approaches have been adopted, such as optical magnification and event centroiding. In this paper, the authors focused on modification of the scintillator. A Gd3Al2Ga3O12:Ce single-crystal scintillator was applied to neutron radiography for the first time and a spatial resolution of 10.5 μm was achieved. The results indicate that this material can be a powerful candidate for a new neutron scintillator providing a resolution in micrometer order by optimizing the optical system and increasing the scintillator luminosity.